Urgensi Revisi UU TPKS: Hilangkan Subjektivitas Laki-Laki Sebagai Pelaku Dan Perempuan Sebagai Korban (Studi Kebijakan Publik Dan Psikologis Gender) - Edward Benedictus Roring; Indira Jazmine; Selma Dwi Anaya Pebriyanti; Eleonora Gracia Puspa Setiawan; FX Adji Samekto (Pemuliaan Keadilan, 2025)
Revision of the Law on Sexual Violence (UU TPKS) has become a strategic urgency in efforts to eliminate gender bias inherent in the current legal construction, especially related to the subjectivity of men as perpetrators and the objectivity of women as victims. The current TPKS Law, although it has provided an important legal basis for the protection of victims of sexual violence, still contains a gender paradigm that limits the understanding that perpetrators of sexual violence are only men and victims are only women, thus ignoring the complexity of social reality and the diversity of victims and perpetrators23. This approach not only reinforces patriarchal stereotypes, but also hinders fair and inclusive law enforcement. Therefore, the revision of the TPKS Law must be directed at eliminating rigid gender constructions, adopting a more neutral and inclusive perspective, and strengthening responsive legal protection for all victims without exception. This revision must also emphasize the role of the state in fulfilling victims' rights and integrating independent monitoring mechanisms to ensure effective and equitable implementation. Thus, the revision of the TPKS Law is not merely a normative update, but rather a transformation of the legal paradigm that prioritizes gender equality, respect for human rights, and substantive justice for the entire community